Comparison of the normal and initial induction curves - Bulte, D; Langman, R (2001)
We present a direct comparison of the normal and initial methods of obtaining an induction curve. It has long been held that ideally the data sets obtained by each method are equivalent; however, acceptable agreement was not experimentally realizable. We propose that, by careful application of contemporary techniques of measuring flux density and field strength, normal and initial induction curves may be obtained that are equivalent within experimental error (approximately 1%). This realization is of great benefit, for although the normal induction curve is the accepted standard for presenting a ferromagnetic profile, data for an initial induction curve are simpler and considerably quicker to obtain by software-controlled data acquisition.